Avaliação da produção de citocinas intracelulares por monócitos e neutrófilos do sangue periférico humano infectados com L. braziliensis: incorporação de um novo parâmetro ao ensaio pré-clínico funcional multiparamétrico baseado em citometria de fluxo - Bruno Generoso Faria (2016)
Therapeutic options for neglected diseases for leishmaniasis’s treatment are still insufficiently and has a problems as a low efficacy, high toxicity and a rise of resistant strains. Associated with this, the reality of the existence of few programs focused in drug discovery for neglected diseases is actually increasing this scenario. In this context, a new and more studies are necessary to discover and develop new potentials compounds with a leishmanicidal activity. In 2012, our group described a standardization of new more complex assay using flow cytometry that enables the access of cytotoxicity and leishmanicidal activity of two drugs that are commonly used in clinical approaches (Glucantime® and Amphotericin B). The new methodology is done through the quantification of internalization rate of labeled-L. braziliensis for monocytes and neutrophils form the human peripheral blood with a simultaneously assessment of cytotoxicity (late apoptosis or necrosis) by flow cytometry. At this study we validated this multiparametric assay when we used Glucantime® and Amphotericin B in human whole blood cultures (n=17 health donors) at the presence or not of live promastigote forms of L. braziliensis. Following this sense, the populations of monocytes and neutrophils were evaluated about the cytotoxic effect, interaction between this phagocytes and L. braziliensis and levels of intracellular cytokines (IL-10, TNF-α and IL-12). The results showed that had a significantly reduction in a quantification of the interaction of the phagocytes with the parasite in cultures with treatment with the two drugs (Glucantime® and Amphotericin B) when we compared with the non-treated cultures. The analysis of the intracellular cytokines profile showed an increase of IL-10, IL-12 and TNF-at the treated cultures with Glucantime® and Amphotericin B in the presence of live promastigote forms of L. braziliensis, enabling the access of different important parameters at drug discovery context. This methodologic innovation is also considered more complex because shows more sensibility as a function of your multiparametric and functional characteristics enabling as a quantitative form, the selection of compounds for new subsequent studies at the different steps of drug discovery programs and can be useful to help in vivo studies in order to reduce the animals used at this phases.